The effect of Plectranthus aliciae (Codd) Van Jaarsv. & T.J. Edwards on quorum sensing of bacteria associated with acne vulgaris - Lall, Namrita (University of Pretoria, 2022)
Thesis (PhD (Medicinal Plant Sciences))--University of Pretoria, 2022.